MORAL VALUES IN THE FILM ENTITLED “MALEFICENT I” BY LINDA WOOLVERTON - Tria Risqa Argareta; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to the moral values which were described by the characters in the “Maleficent” film. The researcher used qualitative descriptive method. Reading the script, watching the movie, and note taking record all data from the script and film were the data collected by the researcher. The researcher used the validity triangulation data and triangulation theory to check validation. The result of the research showed that there are moral values that could be found in the film entitled “Maleficent”, such as honesty, bravery, peaceability, selfconfidence, self-discipline, loyalty, respect, love and affection, kind and friendly, and fair and human that depicted by the characters of Maleficent, Aurora, King Stefan, Diaval, and Prince Philip.   Keywords: Moral values, The Maleficent I movie, Descriptive Qualitatives